(untitled) (Jurnal PkM Pengabdian kepada Masyarakat, 2026)
Task-Based Language Teaching (TBLT) emphasizes meaningful communication through task completion and has been widely applied in English language teaching. In the digital age, the integration of technology into TBLT offers opportunities to increase learner engagement and communicative competence. This community service program aims to introduce English teachers and prospective teachers to the implementation of TBLT integrated with digital tools in narrative text teaching. The program uses a workshop-based approach consisting of theoretical explanations, tool demonstrations, hands-on practice, and reflection sessions. Four digital tools ChatGPT, Bing Image Creator, ElevenLabs, and Canva were integrated into a digital storytelling project titled Fairytales Story Telling. The results show that the integration of TBLT and digital tools improves participants’ pedagogical understanding, digital teaching readiness, and perceptions of student engagement. Despite facing challenges related to technology access, this program demonstrates that technology-supported TBLT provides an effective, student-centered approach to narrative text learning.